Answer:
A) The sequence is {-23, -15, -7, 1,...}
The common difference of the sequence above, d = 8
The first term, a = -23
The number of terms, n = 15
The recursive formula is, aₙ = aₙ₋₁ + d
Using the recursive method gives;
a₅ = a₍₅₋₁₎ + d
Where;
a₍₅₋₁₎ = 1
Therefore, a₅ = 1 + 8 = 9, a₆ = 9 + 8 = 17, a₇ = 17 + 8 = 25, a₈ = 25 + 8 = 33, a₉ = 33 + 8 = 41, a₁₀ = 41 + 8 = 49, a₁₁ = 49 + 8 = 57, a₁₂ = 57 + 8 = 65 a₁₃ = 65 + 8 = 73, a₁₄ = 73 + 8 = 81, a₁₅ = 81 + 8 = 89
The 15th term of the sequence, {-23, -15, -7, 1,...}, a₁₅ = 89
We check by using explicit formula to get, aₙ = a + (n - 1)·d
Therefore
a₁₅ = -23 + (15 - 1)×8 = 89
B) The given sequence is B) {5 5.25, 5.50, 5.75,...}
The common difference, d = 0.25
The first term, a = 5
The required number of terms, n = 15
Using the recursive method gives;
a₅ = a₍₅₋₁₎ + d
Where;
a₍₅₋₁₎ = a₄ = 5.75
Therefore, a₅ = 5.75 + 0.25 = 6
a₆ = 6 + 0.25 = 6.25, a₇ = 6.25 + 0.25 = 6.5, a₈ = 6.5 + 0.25 = 6.75, a₉ = 6.75 + 0.25 = 7, a₁₀ = 7 + 0.25 = 7.25, a₁₁ = 7.25 + 0.25 = 7.5, a₁₂ = 7.5 + 0.25 = 7.75, a₁₃ = 7.75 + 0.25 = 8, a₁₄ = 8 + 0.25 = 8.25, a₁₅ = 8.25 + 0.25 = 8.5
The 15th term, of the sequence, {5 5.25, 5.50, 5.75,...}, a₁₅ = 8.5
We check by explicit formula to get, aₙ = a + (n - 1)·d
Therefore
a₁₅ = 5 + (15 - 1)×0.25 = 8.5
Explanation: